Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11748-010-0594-y
|View full text |Cite
|
Sign up to set email alerts
|

Extrapleural hematoma as a complication following thoracotomy for pulmonary lobectomy

Abstract: Extrapleural hematoma as a complication following thoracic surgery is rare. We report a case of an extrapleural hematoma following pleural lobectomy that resolved completely with nonsurgical treatment. A 63-year-old woman underwent left lower lobectomy for lung cancer through a left posterolateral thoracotomy. She had been prescribed the anticoagulant cilostazol to increase her heart rate for atrioventricular dissociation. Preoperatively, it was stopped, and a temporary pacemaker was placed to counteract brady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“… 5 On the other hand, several cases of EP without episode of trauma were reported. Noguchi et al 1 reported EP as a complication 7 days after posterolateral thoracotomy for left lower lobectomy in an anticoagulated patient followed by a successful conservative therapy. Oka et al 6 reported that two patients with antiplatelet agents complained of pain in their shoulders or backs because of EP that originated from intercostal vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 On the other hand, several cases of EP without episode of trauma were reported. Noguchi et al 1 reported EP as a complication 7 days after posterolateral thoracotomy for left lower lobectomy in an anticoagulated patient followed by a successful conservative therapy. Oka et al 6 reported that two patients with antiplatelet agents complained of pain in their shoulders or backs because of EP that originated from intercostal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…This condition may occur as a complication after blunt chest trauma associated with rib or sternal fractures, which cause injury to the intercostal or parasternal vessels and also be reported as a complication after thoracotomy to be treated conservatively. 1 Here, we present a case of an anticoagulated patient with the sudden appearance of an EP 15 days after thoracoscopic lobectomy, requiring a surgical treatment because of a hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a small EPH and stable patients do not require any interference, and hematoma may resolve spontaneously. [8] However, massive EPH, which causes severe respiratory and circulatory symptoms, requires invasive procedures. In two of our cases, the size of EPH was quite large and was causing shortness of breath.…”
Section: (A) (B) (C)mentioning
confidence: 99%